Virtual Piety and Muslim Traditionalism Mainstreaming: The Digital Activism of Bangkitmedia.com and Kyaiku.com - Rahman, Luthfi (FIKRAH, 2020)
This research focuses on two sites bangkitmedia.com and kyaiku.com which, in the last few years, have been quite intensive in doing digital activism through media sharing about advices and exemplary behaviours of traditional religious clerics or kyai. The phenomenon leads to questioning what behind the digital activism of the two sites is. This paper aims to know and comprehend how such activism within bangkitmedia.com and kyaiku.com has been going through in coloring social media and what message they try to convey to netizens. This is a qualitative research that collects the data from interview and documentation from both websites and analysis them by a digital hermeneutic approach. It found that through the webs, they have built a virtual piety through posted texts or videos that contain religious sermons and testimonies from other people on the religiosity and wisdom of the kyai during and after their lives. Besides, this virtual piety refers to traditionalism mainstreaming which functions as: virtual moderation media and also countering radical narrative.